Analisis Praktik Strategi Negosiasi Integratif dalam Perusahaan Korporat - Aisyah Nurulita Fairuz (Universitas Pendidikan Indonesia, 2022)
Business negotiations have an important role in today's business world. Regardless of the business scale and industrial sector, every company is required to have the right negotiation strategy to maximize its interests, including corporate companies. This article uses the literature review method by analyzing 4 case studies between Lucasfilm and Disney, Apple and Qualcomm, Apple and Netflix, as well as Nokia and Microsoft. From this case study, an analysis is made of how integrative negotiation tactics are applied in competitive business industry and how integrative negotiation can help gain more competitive advantage for corporate companies. The findings of this study prove the importance of an integrative negotiation strategy and suggest corporate companies to build a sense of trust in all parties involved when facing uncertainty during the business negotiation process. The results of this study are expected to explain the theoretical development and practice of the next strategic business negotiation.